KEKERASAN VERBAL DALAM KASUS PENGANIAYAAN ADE ARMANDO DI TWITTER - Unwanus Sidik; Umi Halwati; Nawawi Nawawi (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2022)
Content on social media spreads almost unstoppably, both positive and negative. Due to its virtual nature as well as the fading culture of politeness in society, it can now be seen that uploads or comments in it tend to display harsh and even obscene words called verbal violence. This study aims to determine the form of language used in social media and comments on posts on Twitter social media. This research method uses a qualitative descriptive method. The source of research data comes from social media Twitter, while the data is in the form of uploads and comments on verbal violence on Twitter. The data collection technique uses documentation techniques. Data analysis used qualitative analysis techniques and techniques for checking the validity of the data which was carried out by checking the persistence of observation and checking techniques. The results showed that the form of language used in Twitter sentences has accuracy, clarity, and straightforwardness. While comments on posts on Twitter in the form of verbal violence include: insults, swearing, hyperbole, dysphemism, stigmatization, and associations in animals. The verbal violence on Twitter shows that the Indonesian people do not care about the polite language culture, so that it becomes input for the government and community leaders to find a complete solution in overcoming this quite worrying problem.